Recognition of Human Body Members and Movements For Kindergarten Kids Based on Android - Sapta Purnama, Rizky Fauzi; Rafdhi, Faiz (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2022)
Learning media needs to be used as a supporter of material delivery to reduce failure in communication and maximize the ongoing process of teaching and learning. Early Childhood Education is in dire need of learning media. With android technology based on android smartphones, learning media becomes more interesting, easier and not boring to learn anywhere and anytime. Learning media in android smartphones are better known as learning applications. The MDLC method is an appropriate method in designing and developing a multimedia application which is a combination of image, sound, video, animation and other media. The MDLC method has six stages as follows: Concept, Design, Material Collecting, Assembly, Testing and Distribution. Recognition of Human Body Members and Movements for Kindergarten Children Based on Android. This application is made using the Android Studio programming language as a medium for making and other supporting software to create images of human body parts. The results of developing educational applications as learning media for early childhood can help in understanding and studying each member of their body.